Leadership 2018
DOI: 10.5772/intechopen.76427
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Authentic Leadership on Employees’ Well-Being and the Role of Relational Cohesion

Abstract: Authentic leadership has recently become a matter of significant interest in the fields of politics, economics, society, and culture as well as leadership. This study examines the effects of authentic leadership on employees' well-being and determines whether relational cohesion can regulate the effects that occur between the two. In this regard, the study conducted empirical research with 950 employees of Korea's leading manufacturers, public enterprises, and financial firms. The results demonstrated that tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…However, findings revealed no significant direct effect of AL on perceived stress and stress symptoms. The study by Kim (2018) found an impact of team leaders' AL had a positive significant effect on followers, well-being when relational cohesion was high. Thus, based on the above review on AL and PWB, it can be hypothesised H2.…”
Section: Authentic Leadership and Psychological Well-beingmentioning
confidence: 99%
“…However, findings revealed no significant direct effect of AL on perceived stress and stress symptoms. The study by Kim (2018) found an impact of team leaders' AL had a positive significant effect on followers, well-being when relational cohesion was high. Thus, based on the above review on AL and PWB, it can be hypothesised H2.…”
Section: Authentic Leadership and Psychological Well-beingmentioning
confidence: 99%
“…Also, when knowledge workers perceive that their firms have implemented CSR actions, they tend to expect that their managers will recognize their efforts and promote their personal development. This, in turn, offers them a sense of purpose in their job, which is a crucial element of EWB (Kim, 2018). Perceived CSR also helps promote employees' EWB by cultivating social bonds and building a collaborative climate (Guzzo et al, 2020;Berraies et al, 2020).…”
Section: Effect Of Employees' Well-being On Knowledge Sharingmentioning
confidence: 99%
“…DL may promote employees' EWB by building an empowering work environment in which the latter can collaborate, share knowledge, develop good relationships, and perceive that their managers recognize their efforts and skills and offer them the opportunity to achieve personal growth (Berraies et al, 2021). Leaders' key tasks include assisting employees and let them perceive their work as meaningful, which is an important aspect of EWB (Kim, 2018). In this line, DL improves for employees meaning of work, competence experiences, job autonomy, and impact on firms' performance by allowing them to participate in leadership functions (Jønsson et al, 2016).…”
Section: Mediating Effect Of Employees' Wbmentioning
confidence: 99%
“…DL fulfils such demands through ensuring that these workers operate in an environment where they can encourage one another and seek assistance from other leaders (Khan et al, 2021a;Liao et al, 2019). As such, it decreases the high degree of pressure knowledge workers experience, lowers stress and improves their work-life satisfaction, thereby contributing to their HWB (Kim, 2018). In turn, we expect that employees' HWB and EWB may improve their motivation to share their knowledge and be involved in challenging exploitative and exploratory innovation activities (Berraies et al, 2020;Chumg et al, 2016;Wang et al, 2017).…”
Section: Mediating Effect Of Employees' Wbmentioning
confidence: 99%